Kinerja Peralatan Magnetik Untuk Meningkatkan Performansi Dan Mengurangi Emisi Gas Buang Pada Mesin OTTO Empat Langkah - Tulus Burhanuddin Sitorus; Mulfi Hazwi; Jaya Arjuna (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2019)
National energy data note that Indonesia fossil energy potential consisting of petroleum, natural gas and coal can only last for 10 years, 31 years and 80 years from now if no new fossil energy reserves are found. It is necessary to save energy to anticipate these conditions. One of the efforts that have been done is saving the consumption of fuel oil that is used in the internal combustion engine. This research aims to increase the performance by reducing fuel consumption and exhaust emissions by using magnetic devices. The equipment of magnetic is placed on the intake manifold which is varied 10 cm, 20 cm, and 30 cm from the combustion chamber to determine the effect of installing a magnetic field on the performance of the Otto engine. Gas emission analyzer is placed on the exhaust gas section. Besides that, there were also variations in engine speed consisting of 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, and 4000 rpm. Experimental data show that there is an increase in power and thermal efficiency and a decrease in specific fuel consumption when the engine uses magnetic devices ranging from 5.99-22.02%. The exhaust gas emissions produced by Otto engine also decreased for CO and HC thereabouts 6-20%.